Genetic analysis of beta 2 adrenergic and Dopamine receptor gene polymorphisms in hypertensive subjects at Hospital Seremban, Malaysia - Komara, Makanko (2013)
Essential hypertension which is a major risk factor for cardiovascular diseases is a complex trait influenced by multiple genes and environmental factors. According to The Third National Health and Morbidity Survey in 2008, the prevalence of hypertension among Malaysian adults was 43%. The heritability of hypertension has been estimated to be 60%. B2 adrenoceptor and Dopamine receptor genes have been known to play a major role in blood pressure regulation. This study aims to determine the association of Argl6Gly (rsl042713), Gln27Glu (rs1042714) and Tor] 64lle (rsl800888) polymorphisms of P2 adrenoceptor and A-48G (rs4532) and Taq1A (rs1800497) polymorphism of dopamine receptor in Malaysian hypertensive subjects. A total of 160 of each cases and control subjects were recruited. Systolic blood pressure (SBP), diastolic blood pressure (DBP) and anthropometric measurement were obtained from each subject. Biochemical analysis of lipid profile was measured using auto analyzer. DNA samples were extracted from blood and buccal cells. Genotyping was done by PCR-Restriction Fragment length Polymorphism. SBP, DBP, BMI and biochemical analysis were significantly different between cases and controls (p<0.05). Genotypes of Arg 16Arg, Arg 16Gly and Glyl6Gly among cases were 22.5%, 70% and 7.5% respectively compared to 33.1%, 63.1% and 3.8% respectively among controls. The genotype frequencies of Gln27Gln, Gln27Glu and Glu27Olu among cases were 41.1%, 50% and 1.9% respectively compared to 77.5%, 20.6% and 1.9% respectively among controls. For Thrl64Ile polymorphism, all subjects were homozygote for the wild type genotype. For the Dopamine receptor 1 gene polymorphism, the genotypes frequencies of AA, AG and GG among cases were 54.4%, 38.8% and 6.9% respectively, while the frequencies were 61.2%, 32.5% and 6.2% among control subjects. The genotype frequencies of AlAl, A1A2 and A2A2 of Dopamine receptor 2 gene among cases were 16.2%, 61.9% and 21.95 respectively compared to 14.4%, 50.6% and 35% respectively among control subjects. In this study two polymorphisms were significantly associate with hypertension; Gln27Glu and Taq1A polymorphisms (p = 0.000) and (p= 0.033). In ANOVA analysis, the Age, BMI, SBP, DBP and biochemical analysis results were not significantly associated with study genotypes. The analysis of Multifactor dimensionality reduction showed a significant interaction between P2 adrenoceptor and dopamine receptor genes polymorphism (p=0.001). This study suggests that Gln27Glu and Taq I A polymorphism of P2 adrenoceptor and dopamine receptor genes could be a risk factor associated with hypertension among Malaysians with possible interaction between the genotypes of both genes. known to play a major role in blood pressure regulation. This study aims to determine the association of Argl6Gly (rsl042713), Gln27Glu (rs1042714) and Tor] 64lle (rsl800888) polymorphisms of P2 adrenoceptor and A-48G (rs4532) and Taq1A (rs1800497) polymorphism of dopamine receptor in Malaysian hypertensive subjects. A total of 160 of each cases and control subjects were recruited. Systolic blood pressure (SBP), diastolic blood pressure (DBP) and anthropometric measurement were obtained from each subject. Biochemical analysis of lipid profile was measured using auto analyzer. DNA samples were extracted from blood and buccal cells. Genotyping was done by PCR-Restriction Fragment length Polymorphism. SBP, DBP, BMI and biochemical analysis were significantly different between cases and controls (p<0.05). Genotypes of Arg 16Arg, Arg 16Gly and Glyl6Gly among cases were 22.5%, 70% and 7.5% respectively compared to 33.1%, 63.1% and 3.8% respectively among controls. The genotype frequencies of Gln27Gln, Gln27Glu and Glu27Olu among cases were 41.1%, 50% and 1.9% respectively compared to 77.5%, 20.6% and 1.9% respectively among controls. For Thrl64Ile polymorphism, all subjects were homozygote for the wild type genotype. For the Dopamine receptor 1 gene polymorphism, the genotypes frequencies of AA, AG and GG among cases were 54.4%, 38.8% and 6.9% respectively, while the frequencies were 61.2%, 32.5% and 6.2% among control subjects. The genotype frequencies of AlAl, A1A2 and A2A2 of Dopamine receptor 2 gene among cases were 16.2%, 61.9% and 21.95 respectively compared to 14.4%, 50.6% and 35% respectively among control subjects. In this study two polymorphisms were significantly associate with hypertension; Gln27Glu and Taq1A polymorphisms (p = 0.000) and (p= 0.033). In ANOVA analysis, the Age, BMI, SBP, DBP and biochemical analysis results were not significantly associated with study genotypes. The analysis of Multifactor dimensionality reduction showed a significant interaction between P2 adrenoceptor and dopamine receptor genes polymorphism (p=0.001). This study suggests that Gln27Glu and Taq I A polymorphism of P2 adrenoceptor and dopamine receptor genes could be a risk factor associated with hypertension among Malaysians with possible interaction between the genotypes of both genes.